(NmODELIROWANIE KINETI^ESKIH QWLENIJ W POLUPROWODNIKAH(B. (NmETOD mONTE(B-(NkARLO (B/s - (NiWA]ENKO(B, (NwIKTOR mIHAJLOWI^s; (NmITIN(B, (NwLADIMIR wASILXEWI^s; (NgRIBNIKOW(B, (Nz(B.(Ns(B.s ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 178-190 (289 (NNAZW(B.)s
(Nan ussr(B, (NiN(B-(NT POLUPROWODNIKOWs
Keywords: (NkINETIKAs; (NmATEMATI^ESKIE ISSLEDOWANIQs; (NmONTE(B-(NkARLO METODs; (NpOLUPROWODNIKIs